Are We Having Fun Yet? Institutional Resistance and the Introduction of Play and Experimentation into Learning Innovation through Social Media. Issue 2 (23rd December 2014) - Bryant, Peter; Coombs, Antony; Pazio, Monika
Recognising and responding to behaviours and patterns of resistance is critical to the successful implementation of technology-enhanced learning strategies at higher education institutions. At institutional, academic and student levels, resistance manifests itself in a variety of forms, at best supporting a critical culture and at worst creating inertia and active disquiet. Through the lens of an institution-wide strategic learning innovation vision at the University of Greenwich, designed to enhance connectivity and collaboration, this paper will explore the modes and pathways of resistance that occurred in the process of implementing and embedding an openness agenda at a learning and teaching level. Through supporting experimentation and play with social media creation and sharing as a mechanism of curricula transformation, we identified a number of patterns of resistance to sharing and openness. Using an approach informed by grounded theory we have attempted to represent these patterns in the form of a model of institutional resistance to technology-led change.